Injury Risk Due to Collisions in Major League Baseball - Rosenbaum, D. A.; Davis, S. W. (International Journal of Sports Medicine, 2014)
Purpose is to determine if Major League Baseball plays at risk for collisions have higher injury rates than typical base running plays. 2002–2011 Major League Baseball play data was obtained: non-force putouts by catcher at home plate (Catcher Tag Out), groundball force outs at 2nd base with less than 2 outs (Double Play Attempt), and the control play, outfield assisted non-force putouts of runners attempting to advance to 2nd or 3rd base (Outfield Assist 2nd/3rd). This list was cross-referenced with 2002–2011 disabled lists to see if an involved player went on the disabled list the day of or day after the play. An on-line search for each match determined if the injury was attributable to that play. Rate calculated per 1 000 plays, severity in days on disabled list. Injury rate and severity for Catcher Tag Out was 6.98 and 45.6 respectively, Double Play Attempt 0.42 and 41.3, Outfield Assist 2nd/3rd 1.56 and 47.0. Injury rate for Catcher Tag Out was higher (P=0.03) than the control while Double Play Attempt trended lower (P=0.05). There was no difference in severity. Catcher Tag Outs carry greater injury risk than typical base running plays. Major League Baseball should consider prohibiting base path collisions.
Keywords: baseball; injury; collision; rules; catcher